Antigen Uptake by Langerhans Cells Is Required for the Induction of Regulatory T Cells and the Acquisition of Tolerance During Epicutaneous Immunotherapy in OVA-Sensitized Mice - Dioszeghy, Vincent; Mondoulet, Lucie; Laoubi, Leo; Dhelft, Véronique; Plaquet, Camille; Bouzereau, Adeline; Dupont, Christophe; Sampson, Hugh (Frontiers in Immunology, 2018)
The skin is a major immunologic organ that may induce protection, sensitization or tolerance. Epicutaneous immunotherapy (EPIT) has been proposed as an attractive strategy to actively treat food allergy and has been shown to induce tolerance in sensitized mice through the induction of Foxp3+ regulatory T cells (Tregs), especially CD62L+ Tregs. Among immune cells in the skin, dendritic cells are key players in antigen-specific immune activation or regulation. The role of different populations of skin DCs in tolerance induction remains to be elucidated. Using OVA-sensitized BALB/c mice, we demonstrated that the application of a patch containing OVA-A647 to the skin resulted in allergen uptake by Langerhans cells (LCs) and CD11b+ dermal cDC2 and subsequent migration into skin draining lymph nodes. These 2 populations induced Foxp3 expression in CD4+ cells in vitro. Only LCs induced LAP+ cells and CD62L+ Tregs. Using Langerin-eGFP-DTR mice, we analyzed the role of LCs in the mechanisms of tolerance induction by EPIT in vivo. Following complete depletion of LCs, a dramatic decrease in the number of OVA+ DCs and OVA+ CD11b+ dermal cDC2 was observed in skin draining lymph nodes 48h after epicutaneous application. Likewise, 2 weeks of EPIT in non-depleted mice induced Foxp3+ Tregs, especially CD62L+, and LAP+ Tregs in skin draining lymph nodes and spleen, whereas no induction of Tregs was observed in LC-depleted mice. Following 8 weeks of treatment, EPIT-treated mice showed significant protection against anaphylaxis accompanied by a significant increase of Foxp3+ Tregs, especially CD62L+ Tregs, which was not seen in the absence of LCs. In summary, although both LCs and CD11b+ dermal cDC2s could induce regulatory T cells, the absence of LCs during EPIT impaired treatment efficacy, indicating their crucial role in skin-induced tolerance.